Challenging the conventional wisdom on enterprise: Control and autonomy in a direct selling organisation - Claudia Groß; Nicole Jung (Management Revue, 2009)
Entrepreneurialism within organisations has been praised for serving employees and employers alike, but it has also been criticised as exercising power over employees in an unobtrusive, yet effective way. Within the literature from both advocates and critics, two dichotomies prevail. First, 'enterprise' is considered as a monolithic concept that is either 'liberating' or governing employees; second, it tends to be viewed as strongly opposed to 'bureaucracy'. Recent studies have started to challenge these hitherto often one-sided characterisations by showing that individuals react and respond differently to entrepreneurialism and that bureaucratic elements can co-exist within entrepreneurial companies. However, by drawing on empirical evidence from an entrepreneurial company, we demonstrate that enterprise within an organisation itself is a complex and paradoxical instrument of power and governance in organisations. We suppose that enterprise cannot stand on its own but is instead based upon organisational practices that are at the same time liberating and controlling, entrepreneurial and bureaucratic. Such a view not only allows one to pay attention to the fractions that are caused when the ideal of the individual self-made man is transferred to organisations, but also to question the enterprise discourse itself.
Keywords: 650; enterprise; power; normative control; bureaucracy; direct selling